Politeness Strategy in The 2024 Presidential Candidate Debate - Sukardi, Sukardi; Afan, M; Wahidah, Nurul; Nur’aini, Anisa (Interference: Journal of Language, Literature, and Linguistics, 2024)
Abstract. Debate is one of the means that can be utilized by each presidential candidate to convey the vision and mission. Debates are part of the public's attention to find out the quality of the nation's prospective leaders. The success of conveying the vision and mission and attracting public attention is highly dependent on the language strategies used. This study discusses the politeness strategies used by each presidential candidate in the 2024 presidential debate. This research aims to identify politeness strategies used by presidential candidates in debates and to assess the role of politeness strategies in maintaining the quality of debates and relationships between presidential candidates. The type of research used is qualitative research. The researcher acts as the main instrument and observation guidelines is as supporting instrument in collecting data in this research. The result of study reveals that in the 2024 presidential debate there are three politeness strategies used: positive politeness, negative politeness, and bald on record. However, there are two most dominant politeness strategies used in the debate; positive politeness and bald on record. The both politeness strategies show that all candidates still uphold the principles of politeness in debating, being respectful and harmonious, trying to keep face of their debate opponents and maintaining the quality of clarity and accuracy of opinions conveyed.  The both politeness strategies have a very effective role in in attracting public attention, delivering vision and mission, and maintaining relationship. Keywords: Politeness, Communication, Presidential Candidate Debate